Porous MnO2/CNT catalysts with a large specific surface area for the decomposition of hydrogen peroxide - Kim, Min June; Lee, Kang-Bong; Seo, Myung-gi; Lee, Kwan-Young (KOREAN INSTITUTE CHEMICAL ENGINEERS, 2017)
H2O2 vapor sterilization is an effective and safe method for removing various pathogens. To improve the efficiency of this technique, the time required for sterilization must be shortened. The aeration time constitutes a large portion of the total sterilization time; therefore, the development of a catalyst for H2O2 decomposition is necessary. Bulk MnO2 is typically used in H2O2 decomposition, but it has a low specific surface area. To increase H2O2 decomposition activity, specific surface area and electron transfer ability of catalyst need improvement. In this study, MnO2/CNT(x), where x denotes the weight ratio of CTAB to H2O in the catalyst preparation, was synthesized using a soft template method with varying amounts of the template. Overall, the catalyst specific surface area remarkably increased to 190-200 m(2)/g from 0.043 m(2)/g for bulk MnO2 and these increased surface areas resulted in superior H2O2 decomposition activity. Among the CNT-supported catalysts tested, MnO2/CNT (1.0) exhibited the highest activity, which was 570 times that of bulk MnO2. Aeration times were also calculated with some assumptions and the aeration can be finished within 1 hr (bulk MnO2 needs about 25 hr).
Keywords: ETHYLENE-OXIDE; STERILIZATION; OXYGEN; MECHANISM; GAS